Análisis financiero y su incidencia en la toma de decisiones de la empresa Agroindustrial Laredo S.A.A., años 2015-2016 - Véliz Pacheco, Lourdes Gisella (2019)
The objective of the present investigation is to determine how the financial analysis affects the company's decision making of Agroindustrial Laredo SAA, 2015-2016, and includes a progressive development of the different stages that It starts from the bibliographic collection and review of documents of the business unit to the processing of data collected in the field, elaboration and analysis of the results that allow to integrate all the variables according to the proposed problem. The methodology used, will be obtained through the analysis of the company's financial statements (the statement of financial position and the income statement) and a questionnaire. This research is generated with the application of a quantitative research method to generate valid and reliable knowledge within the area of finance, accounting and financial sciences. Finally, it was evidenced that the financial analysis shows an increase in the sales in reference of the year 2015, which allowed to generate investments to develop and implement the business portfolio of products and sub-products of added value elaborated from renewable sources such as vinasse , so it is recommended to prepare an analysis of the statements of financial position at the end of the exercises, to compare them with previous years, in this way to know the percentage variations of assets, liabilities and equity annually, to analyze these variations and make a Examination of the reason for said results.